A Study of the repayment difficulties of the microfinance borrower households of the Ahon Sa Hirap Inc. (ASHI) - ACEVEDO, JAIME MARIE (Archīum Ateneo, 2017)
This research studies the loan repayment difficulties of borrower households of the Ahon saHirap Inc. (ASHI), a social mission-oriented Philippine microfinance institution. Theprincipal investigation of the research examines whether the repayment performance of ASHI borrower households conforms to theoretical expectations based on a model of microfinance repayment behavior developed by Gonzalez (2008) augmented by some analyticalextensions. Data on 404 ASHI borrower households belonging to three ASHI branches inRizal province reveals that 68 borrower households, or 16.8 % of the total, did not pay in fulla weekly loan obligation on at least one occasion during their respective 2012-13 repayment observation period. Econometric analysis of the said data reveals the following: a greaterlikelihood that a borrower household has per capita income below the official povertyline increases the probability that the said household does not pay in full a weekly loanobligation. Altogether, the research empirical results provide validation for the repaymentmodel of Gonzalez (2008) and its analytical extensions developed by the research. Theresults, moreover, support the on-going effortamong both microfinance analysts andpractitionersto reframe the poverty alleviation agenda of microfinance, moving it awayfrom a narrow emphasis on its promotional/ income-generating role toward a greaterappreciation of its protectional/ consumption smoothing function.